The academic gender gap take phenomenon: the application of TRA to the behavioral beliefs of female students toward accounting discipline in IIUM and TARC - Zandi Pour Joopari, GholamReza; Sulaiman, Mohamed; Naysary, Babak (2013)
The aim of this study is to examine the factors affecting Malaysian male and female students’ intention to enroll in accounting program. The study is based on the Theory of Reasoned Action (TRA) as a theoretical framework. Based on TRA model, the factors that may affect students’ behavioral intention to choose accounting program are categorized into three dimensions: attitudes toward choosing accounting program (ATT), subjective norm (SN) and amount of information on accounting (AIA). The questionnaire is employed to collect data from a sample of 400 male and female students in IIUM and TARC in Malaysia currently enrolling in accounting program. According to our results ATT and SN have significant influence on behavioral intention of both male and female students to enroll in accounting program. In case of AIA, the results support its significant impact on males but not females’ behavioral intention to enroll in accounting program. Several implications and recommendation are also discussed in the light of our findings.